Study of Some Toxic Effects of Diminazine in Vitro - IM, Taj Eldin; OY, Mohamed; AH, Mohamed; MA, Elhadi (مجلة الجزيرة للعلوم الصحية; مجلد 8 عدد 2 (2012), 2012)
Background: The trypanocidal agent, diminazine have been shown to produce some toxic effects such as itching, hypotension and gastrointestinal disturbances among the migratory domestic animals, especially in camels during the dry season in South-western Sudan.                                                                  Objective: The present study was an attempt to explain some toxic effects of diminazine in vitro. Methods: A number of qualitative and quantitative experiments have been done to elucidate these mechanisms using different concentrations of diminazine.  Results: Incubation of different concentrations of diminazine with rat lung chops and their intraperitoneal administration, produced incubates that potently stimulated the isolated guinea-pig ileum. The obtained contractions were dosedependent and effectively blocked by the anti-histamine, diphenhydramine. The yielded incubated mixtures when developed on paper chromatography with authentic samples showed two spots with R f values and colours similar to those of heparin and histamine when sprayed with ninhydrin or exposed to iodine vapour. The extent to which diminazine released histamine was determined by measuring the concentrations of the released histamine using the three-point assay. The addition of EDTA, diltiazem and dinitrophenol separately to the incubated mixtures indicated that the release of histamine and the accompanied heparin was calcium-and energy-dependent, most probably by exocytosis and damaging the lung and peritoneal mast cells.  When tested on isolated rabbit jejunum, diminazine was found to potentiate the effect of histamine with pA1/2 value of 5.4 ± 0.13 compared to 5.6 ± 0.15 for aminoguanidine, the standard diamine oxidase inhibitors. Conclusion: Diminazine was found to have a potent histamine releasing capacity. These findings indicated that the severe toxic effects produced by diminazine might be due to its ability to release histamine and/or potentiating its effects.